2015
DOI: 10.1186/s13104-015-1781-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of work ability and work-related physical activity of employees in a medium-sized business

Abstract: BackgroundWork-related physical activity (PA) and work ability are of growing importance in modern working society. There is evidence for age- and job-related differences regarding PA and work ability. This study analyses work ability and work-related PA of employees in a medium-sized business regarding age and occupation.MethodsThe total sample consists of 148 employees (116 men—78.38 % of the sample—and 32 women, accounting for 21.62 %; mean age: 40.85 ± 10.07 years). 100 subjects (67.57 %) are white-collar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
8
1
1
Order By: Relevance
“…Our first hypothesis, that OPA would be negatively associated with PWA, was not confirmed in our data. This finding is not in line with previous research, which, using a self-reported questionnaire, showed that white-collar workers, that is sedentary jobs, had higher PWA compared to blue-collar workers, that is physically active jobs (Wilke et al, 2015). A possible explanation for the lack of associations between OPA and PWA in our study might be found on the methodological level.…”
Section: Discussioncontrasting
confidence: 99%
“…Our first hypothesis, that OPA would be negatively associated with PWA, was not confirmed in our data. This finding is not in line with previous research, which, using a self-reported questionnaire, showed that white-collar workers, that is sedentary jobs, had higher PWA compared to blue-collar workers, that is physically active jobs (Wilke et al, 2015). A possible explanation for the lack of associations between OPA and PWA in our study might be found on the methodological level.…”
Section: Discussioncontrasting
confidence: 99%
“…49 The beneficial relation between various parameters of physical activity and work ability has been recognized in many previous studies. 30,31,50,51 Also, some studies have shown that physical exercise can reduce musculoskeletal problems and pain among both adults 25,52 and older people. 24,53 In our study, similar results were observed in women aged 50-64 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the significant relationship between physical activity and the ability to work. [29][30][31] Work ability can be defined as having the health, competence and relevant occupational virtues required for managing some kind of job, assuming that the work tasks are reasonable and that the work environment is acceptable. 32 Therefore, it should be noted that the concept of work ability is holistic and can be affected by various factors, such as, eg, work stressors, individual characteristics, and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To meet these needs successfully, workers must have the corresponding physical, mental and social abilities. The working ability is also closely related to workers' professional experience, psychological state, work motivation, and so on [27]. Many studies have confirmed the impact of job burnout on work ability.…”
Section: Introductionmentioning
confidence: 99%